PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WALI MURID DI SD MUHAMMADIYAH KUTOARJO - Pujo Raharjo (Prospect : Jurnal Manajemen dan Akuntansi, 2022)
The aim of this research is to find out whether there is a positive and significant influence between the quality of educational services on the satisfaction of parents at SD Muhammadiyah Kutoarjo. This research is quantitative descriptive research because the research data uses numbers to conclude the results of research conducted at SD Muhammadiyah Kutoarjo. The population of this study was all 110 parents of 6th grade students at SD Muhammadiyah Kutoarjo. The sample used was 110 parents using a saturated/census sample. This research uses data analysis methods, namely: simple correlation, simple regression, coefficient of determination, and t test. Based on research by the author, a simple regression result was finally obtained, namely Y = 7.517+ 0.669(X). The results of the calculation of the coefficient of determination show an R Square figure of 0.384 or 38.4%. This figure means that 38.4% of parent satisfaction is influenced by the service quality variable. While the remaining 61.6% is influenced by other variables outside the research such as educational quality factors, tuition fees, educational technology, costs and convenience. This research shows the results of the service quality variable are 1.982, the service quality variable is 8.205 with a sig value of 0.000 so Ha was accepted, then Hoyang stated that there was no positive and significant influence between service quality variables on the satisfaction of parents at SD Muhammadiyah Kutoarjodilak.